Positive and Negative Themes Found in Sport-Related Films. (June 2017) - Wakefield, Hannah M.; Olympia, Robert P.; King, Tonya S.; Wakefield, Bryan H.; Weber, Chris J.
Sport participation is an important part of the development of children and adolescents in the United States. The objective of this study was to determine positive and negative themes found in a selected number of sport-related films. A total of 44 sport-related films were independently viewed and analyzed by four reviewers. The most common sports depicted were baseball (27%) and football (25%). The most common positive themes were positive interactions with the coach, positive interactions with family and friends, and positive interactions with teammates (2.04, 1.42, 1.2 mean events per hour). The most common negative themes were taunting/fighting/poor sportsmanship, negative interactions with the coach, and drinking/smoking/drug use (2.13, 1.10, 0.94 mean events per hour). In conclusion, the coviewing of sport films among pediatric athletes and their coaches, athletic trainers, and/or parents in order to focus on "teachable moments" may encourage the acquisition and development of positive themes and the avoidance and de-emphasis of negative themes.